2016
DOI: 10.3389/fphys.2016.00351
|View full text |Cite
|
Sign up to set email alerts
|

20-Hydroxyeicosatetraenoic Acid (20-HETE) Modulates Canonical Transient Receptor Potential-6 (TRPC6) Channels in Podocytes

Abstract: The arachidonic acid metabolite 20-hydroxyeicosatetraenoic acid (20-HETE) regulates renal function, including changes in glomerular function evoked during tubuloglomerular feedback (TGF). This study describes the cellular actions of 20-HETE on cultured podocytes, assessed by whole-cell recordings from cultured podocytes combined with pharmacological and cell-biological manipulations of cells. Bath superfusion of 20-HETE activates cationic currents that are blocked by the pan-TRP blocker SKF-96365 and by 50 μM … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 69 publications
0
20
0
Order By: Relevance
“…Most of the macroscopic ionic current in podocytes that is activated by native G protein signaling or other stimuli can be attributed to TRPC6-containing channels on the basis of sensitivity to TRPC6 knockdown, La 3+ and SKF-96365 [36,38,39] and SAR7334 (the present study). However, TRPC5 channels are also expressed in podocytes [48,51] and have been proposed to play a role in the progression of kidney disease [69], although the factors that normally cause them to become active are not known.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…Most of the macroscopic ionic current in podocytes that is activated by native G protein signaling or other stimuli can be attributed to TRPC6-containing channels on the basis of sensitivity to TRPC6 knockdown, La 3+ and SKF-96365 [36,38,39] and SAR7334 (the present study). However, TRPC5 channels are also expressed in podocytes [48,51] and have been proposed to play a role in the progression of kidney disease [69], although the factors that normally cause them to become active are not known.…”
Section: Discussionmentioning
confidence: 64%
“…Filters were probed using primary antibodies, washed, incubated with horseradish peroxidase-conjugated secondary antibodies, and visualized using chemiluminescence. Methods for cell surface biotinylation assays to measure steady-state surface abundance of TRPC6 channels were also described previously [37,39,4749]. Rabbit antibodies against TRPC6 (ACC-017) and TRPC5 (ACC-020) were obtained from Alomone Labs (Jerusalem, Israel), antibodies against podocin (sc-21009) and β3-integrin (sc-14009) were obtained from Santa Cruz (Santa Cruz, CA).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…136 Thus, 20-HETE has been suggested to contribute to diabetic nephropathy. 138,[140][141][142] Roshanravan et al 143 recently reported that 20-HETE increases TRPC6 activity in podocytes secondary to activation of ROS production. Activation of TRPC6 causes foot process effacement, [144][145][146][147] but paradoxically, effacement prevents podocyte detachment.…”
Section: -Hetementioning
confidence: 99%
“…TRPC6 is confirmed to be a nonselective cation channel. A large body of studies [23,24] strongly support that TRPC6 is an essential functional component of TRPCs in vascular smooth muscle cells. It has been shown that activated TRPC6 regulates its contractile function by permeating cation influx and depolarization of vascular smooth muscle cells [25].…”
Section: The Role Of Trpcs In Kidney Diseasementioning
confidence: 99%